2023
DOI: 10.1038/s41419-023-05753-9
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-based nanoimmunotherapy targeting TAMs, a promising strategy for glioma

Abstract: Exosomes, the cell-derived small extracellular vehicles, play a vital role in intracellular communication by reciprocally transporting DNA, RNA, bioactive protein, chains of glucose, and metabolites. With great potential to be developed as targeted drug carriers, cancer vaccines and noninvasive biomarkers for diagnosis, treatment response evaluation, prognosis prediction, exosomes show extensive advantages of relatively high drug loading capacity, adjustable therapeutic agents release, enhanced permeation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 233 publications
0
21
0
Order By: Relevance
“…Previous studies have demonstrated that patients with glioma exhibit limited sensitivity to immunotherapy ( Yu and Quail, 2021 ). However, the identification of advanced immunotherapy regimens ( Luo et al, 2023 ; Morimoto et al, 2023 ), and emerging treatment targets ( Zhuo et al, 2023 ) is anticipated to overcome this obstacle. Upon examining the three cohorts, we observed that patients with an elevated IGF1RS exhibited a heightened response to anti-PD1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that patients with glioma exhibit limited sensitivity to immunotherapy ( Yu and Quail, 2021 ). However, the identification of advanced immunotherapy regimens ( Luo et al, 2023 ; Morimoto et al, 2023 ), and emerging treatment targets ( Zhuo et al, 2023 ) is anticipated to overcome this obstacle. Upon examining the three cohorts, we observed that patients with an elevated IGF1RS exhibited a heightened response to anti-PD1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent these challenges, new approaches are highly required; as the burgeoning strategies, targeted multifunctional theranostic nanoformulation of CU opens up new opportunities in precision medicine thanks to its potency for accurate diagnostic and combinational therapy having minimal invasiveness, high selectivity, and low toxicity. 14 Herein, few reports are already available in literature, indicating the efficacy of CU-based nanoformulations to treat various cancers including breast cancer. As an example, Verderio et al had incorporated CU in polylactic-co-glycolic acid (PLGA), checked the chemical stability within the cellular environment and investigated antiproliferative activity against estrogendependent MCF-7 breast cancer cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In order to overcome the limitations, researchers have tried to increase bioavailability by using several adjuvants to block CU metabolism or to modify CU structure, etc., but they are well below from the satisfactory level. To circumvent these challenges, new approaches are highly required; as the burgeoning strategies, targeted multifunctional theranostic nanoformulation of CU opens up new opportunities in precision medicine thanks to its potency for accurate diagnostic and combinational therapy having minimal invasiveness, high selectivity, and low toxicity . Herein, few reports are already available in literature, indicating the efficacy of CU-based nanoformulations to treat various cancers including breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, immunotherapy against TAMs and the design of its delivery system is of great importance in the field of tumor therapy. Currently, the primary immunotherapeutic strategies targeting TAMs comprise hindering TAM recruitment, eliminating TAMs, and adjusting TAM polarization [ 4 , 5 ]. Macrophages are functionally flexible and, as is established, can polarize to the pro-inflammatory/anti-tumorigenic M1-like or anti-inflammatory/pro-tumorigenic M2-type [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%